(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
University Medical Centre, Human Movement Sciences, School of Sports Studies & University of Groningen, Hanze University of Applied Sciences, Groningen, The Netherlands Globally, the COVID-19 pandemic has had a significant effect on people’s mental health and levels of physical activity, especially in older adults who are more vulnerable. Although it has been five years since the beginning of the COVID-19 pandemic, many older adults still face direct and indirect negative consequences such as mental health issues, feelings of loneliness, and a lower quality of life. Additionally, society and older adults should be better prepared and become more resilient for unforeseen pandemics in the future. The aim of the BASE project is to bring older adults back to society both physically and socially through a peer-to-peer approach. Sport and Health professionals (BASE mentors) in Spain, North Macedonia, Portugal, and Lithuania were trained to educate volunteering local older adults (BASE Buddies) who supported the older adults targeted by the BASE project. The content of the BASE programme centred around the topics of healthy lifestyle, behavioural change, and a neighbourhood approach. An evidence-informed process was followed, including a rapid review to find and analyse recent scientific literature on these three topics. Additionally, short interviews were conducted with older adults to better understand their perspectives on these topics. Moreover, the expertise of sports and health professionals was collected to specifically define the topics in the context of BASE and translate them into concrete and actionable themes in the BASE training programmes for the BASE mentors and Buddies. In the BASE training programmes, healthy lifestyle was defined as being physically active with some attention to nutrition aspects. Furthermore, a broad and holistic definition of health was favoured. Six behavioural change determinants/techniques regarding physical activity were prioritised for BASE: 1) Barrier identification; 2) Providing rewards; 3) Modelling; 4) Self-efficacy; 5) Social support; 6) Enjoyment. Finally, a neighbourhood was not only considered as a geographical area where adults live but also seen as a contributor or agent that stimulates a sense of collectiveness and social interaction. Concrete examples of the translation of these topics in the BASE programme will be illustrated during the presentation. Acknowledgement: The Erasmus+ BASE project was co-funded by the European Union. Keywords: Older adults, healthy lifestyle, behavioural change, neighbourhood approach, peer-to-peer training